2018
DOI: 10.1111/jocn.14295
|View full text |Cite
|
Sign up to set email alerts
|

A rating instrument for fear of hospitalisation

Abstract: Identification of patients with high level of fear of hospitalisation by this instrument should help clinicians to administer measures which may decrease fear and prevent avoidance of healthcare utilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The FH scale is a 17-item scale developed by Dr. Slobodan M. Jankovic et al to comprehensively measure the fear of hospitalization experienced among outpatients ( Jankovic et al, 2018 ). The FH scale includes three dimensions: Factor 1: Fear of being injured (7 items), Factor 2: Mistrust to the medical staff (5 items), and Factor 3: Fear of losing privacy, autonomy, and family ties (5 items).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FH scale is a 17-item scale developed by Dr. Slobodan M. Jankovic et al to comprehensively measure the fear of hospitalization experienced among outpatients ( Jankovic et al, 2018 ). The FH scale includes three dimensions: Factor 1: Fear of being injured (7 items), Factor 2: Mistrust to the medical staff (5 items), and Factor 3: Fear of losing privacy, autonomy, and family ties (5 items).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above, there is a need for reliable instruments to assess patients’ fear of hospitalization in China objectively. Professor Slobodan M. Jankovic developed and validated the FH scale ( Jankovic et al, 2018 ) based on the guidelines developed by DeVellis (1991) . Therefore, this study aimed to translate the FH scale into Chinese and validate its psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We got permission for translation and cross-cultural adaptation from the authors of the Fear of COVID-19 scale ( 3 ). We also got permission for using the Fear of Hospitalization scale as well as for the Emotional Regulation Questionnaire (ERQ) ( 29 , 30 ). The original version of the scale was translated from English into Serbian by two English speakers, a professional translator and a bilingual university professor.…”
Section: Methodsmentioning
confidence: 99%
“…While at the hospital, the patient has anxiety and worry due to poor communication with staf, waiting for surgery, fear of dying, fear of the unknown, and some unmet needs [1][2][3]. Other factors contributing to fear of hospitalization include the efects of the disease, being away from family, and a lack of confdence in medical professionals [2,4]. Evidence has also revealed that awareness of self-care behaviors, nurse behavior, level of health literacy, depth of knowledge, kind of illness, education, occupation, sex, and age are all linked to fear of hospitalization [5,6].…”
Section: Introductionmentioning
confidence: 99%